La Comisión Brandt : una perspectiva latinoamericana - Botero, Rodrigo (Estudios Internacionales, 1979)
The Brandt Commission arises from the initiative to convene an ad hoc non-governmental forum to carry out a completely independent review of the North-South problem, including both the problems of industrialized countries and those of developing countries, and make some recommendations to the international community. The leitmotif chosen for the Commission’s work was that of mutual interests, precisely because its emergence was due to the fact that the international community came to feel that the confrontational scheme, that is, the scheme based on intergovernmental discussions inspired due to radically antagonistic positions, did not advance. There are high expectations about the results of the Commission’s report; however, the receptivity of this report will depend, to a large extent, on unpredictable factors.